2003
DOI: 10.1590/s0102-76382003000100013
|View full text |Cite
|
Sign up to set email alerts
|

Partial left ventriculectomy in a child: 70-month clinical follow up

Abstract: Ventriculectomia parcial esquerda em criança: acompanhamento clínico por 70 meses Work performed in the institute of D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 4 publications
(6 reference statements)
1
4
0
Order By: Relevance
“…Yamagishi et al [ 10 ] and Westaby et al [ 11 ] present separately a female child case, one is 3 years old and the other is only 5 months old, both with ischemic DCM caused by anomalous origin of the left coronary artery of pulmonary artery, submitted to PLV. In both cases, and in agreement with the results of Souza et al [ 7 ] study, after performing the procedure, the kids have already presented very significant improvements in LV function, sharp reduction in the cavity volume and great improvement in FS. However, only Westaby et al [ 11 ] performed monitoring, and it is reported that in the last assessment the child was already 10 years old, in NYHA class I, played sports and had normal mental and physical development, showing great results at long term.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…Yamagishi et al [ 10 ] and Westaby et al [ 11 ] present separately a female child case, one is 3 years old and the other is only 5 months old, both with ischemic DCM caused by anomalous origin of the left coronary artery of pulmonary artery, submitted to PLV. In both cases, and in agreement with the results of Souza et al [ 7 ] study, after performing the procedure, the kids have already presented very significant improvements in LV function, sharp reduction in the cavity volume and great improvement in FS. However, only Westaby et al [ 11 ] performed monitoring, and it is reported that in the last assessment the child was already 10 years old, in NYHA class I, played sports and had normal mental and physical development, showing great results at long term.…”
Section: Resultssupporting
confidence: 90%
“…Another interesting study that indicates positive results after completion of the PLV, as the one presented by Sugiyama et al [ 5 ] is the study performed by Coelho de Souza et al. [ 7 ] . In his study, only one child diagnosed with idiopathic DCM has been undergoing the procedure and monitored for 70 months.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations